Effect of gaseous hydrogen embrittlement on the mechanical properties of additively manufactured CrMnFeCoNi high-entropy alloy strengthened by in-situ formed oxide - Kim, Young-Kyun; Suh, Jin-Yoo; Lee, Kee-Ahn (ELSEVIER SCIENCE SA, 2020)
Effect of gaseous hydrogen charging on the mechanical properties of additively-manufactured CrMnFeCoNi high-entropy alloy (HEA) strengthened by in-situ formed oxide was investigated. The results showed that SLM-built HEA exhibited yield strength of similar to 729.6 MPa and has an excellent hydrogen embrittlement resistance due to high-hydrogen solubility and easy deformation twin formation.
Keywords: MICROSTRUCTURE; BEHAVIOR; RESISTANCE; METALS